KARAKTERISTIK PASIEN APENDISITIS BERDASARKAN SKOR RIPASA DI RUP DR. M. DJAMIL PADANG - Mhd Nurhuda; Rosmaini Rosmaini; Yusti Siana; Muhamad Ivan; Fazilla Arma (Nusantara Hasana Berdikari, 2022)
Acute Appendicitis Is An Inflammation Of The Appendix Vermiformis. The Research Find Out Characteristics Of Appendicitis Patients Based On RIPASA Score At Dr. M. Djamil General Hospital For The Period January 2017 – December 2019. Type Of This Research Is Categorical Descriptive With Cross Sectional Approach Using Secondary Data. The Sample Was 93 Acute Appendicitis Patient Who Were Recorded In The Medical Records Of Dr. M. Djamil General Hospital And Were Selected Using Purposive Sampling Techniques. Data Processing Using The SPSS Program. Result Of Research Are The Most Gender Were Male (60 Patients, 64,5%) With The Most Age Group Were <39,9 Years (68 Patients, 73,1%). RIF Pain Found In 93 Patients (100%), Migration Pain To The RIF Found In 63 Patients (67,7%), Anorexia Found In 21 Patients (22,6%), Nusea And Vomiting Found In 77 Patients (82,8%). The Most Duration Of The Symptoms Were <48hours (49 Patients, 52,7%). RIF Tenderness Found In 93 Patients (100%), Guarding Found In 49 Patients (52,7%), Rebound Tenderness Found In 70 Patients (75,3%), Increase Body Temperature Found In 51 Patients (54,8%) And The Most Leukocytes Level Were >10.000sel/µl (74 Patients, 79,6%).Variable Of RIPASA Can Be Used As Characteristic Appendicitis Patients The Abstract Consists Of A Single, Concise Paragraph Describing The Purpose, Procedure, And Results Of Your Study. Use No More Than 200 Words. Do Not Write The Abstract Until You Are Nearly Finished Writing And Then Draft And Redraft Until It Reads As Clearly As Possible.